Evaluating lean implementation performance in Indian MSMEs using ISM and AHP models. (2015) - Ravikumar, M.M.; Marimuthu, K.; Parthiban, P.
This paper investigates the implementation of the lean manufacturing concepts in Indian MSMEs. In particular, it examines the extent to which lean can be implemented given the various financial constraints businesses find themselves in the current economic environment in India. Here a new method combined with interpretive structural modelling (ISM) and analytical hierarchy process (AHP) models were used to evaluate the lean implementation performance of MSMEs. After finding the weights for those criteria, these were ranked. The AHP model was applied to find the best one in lean implementation from a group of six MSMEs. Further, to justify the AHP results, fuzzy was used to compare those criteria weights. This paper presents an innovative method to ascertain how a set of 11 factors can influence successful lean implementation. The analysis of AHP and ISM methodologies provides the industry with an insight on how lean implementation can be made more responsive.